2005
DOI: 10.1007/bf03018588
|View full text |Cite
|
Sign up to set email alerts
|

Low dose intrathecal morphine facilitates early extubation after cardiac surgery: results of a retrospective continuous quality improvement audit

Abstract: P Pu ur rp po os se e: : To document one centre's experience with a multimodal analgesic approach, with or without low dose intrathecal morphine (ITM), in facilitating "fast-track" recovery in patients undergoing cardiac surgery.M Me et th ho od ds s: : Records of 131 consecutive patients who underwent first time elective cardiac surgery during a four-month period in 2000 were reviewed. Patients were divided into two groups: those receiving and those not receiving preoperative low dose ITM (< 5 µg·kg -1 ) as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
6
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
4
6
0
2
Order By: Relevance
“…Mehta et al reported that addition of 8 μ/kg intrathecal morphine to a fentanil based general anesthesia provided superior quality of analgesia and facilitated early extubation 11 . These results agreed with Parlow et al in their retrospective, multimodal study who found that less than 5 μ/kg spinal morphine reduced need for postoperative analgesic 12 . A retrospective study using an average dose of 13 μg −1 spinal morphine combined with a fentanil based general anesthesia in off‐pump CABG surgery also showed profound and long‐lasting postoperative analgesia and facilitated early extubation 13 .…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Mehta et al reported that addition of 8 μ/kg intrathecal morphine to a fentanil based general anesthesia provided superior quality of analgesia and facilitated early extubation 11 . These results agreed with Parlow et al in their retrospective, multimodal study who found that less than 5 μ/kg spinal morphine reduced need for postoperative analgesic 12 . A retrospective study using an average dose of 13 μg −1 spinal morphine combined with a fentanil based general anesthesia in off‐pump CABG surgery also showed profound and long‐lasting postoperative analgesia and facilitated early extubation 13 .…”
Section: Resultssupporting
confidence: 70%
“…Several studies evaluated the effect of ITM on postoperative pain, extubation times, and intensive care unit (ICU) length of stay with conflicting results. Some of these studies revealed that ITM provided adequate analgesia and facilitate early extubation, 11–15 whereas the others resulted with inadequate postoperative analgesia or prolonged ventilatory depression 16–18 . Considering these data, it is difficult to reach a decision about the real efficacy of ITM because different doses and different anesthetics were used in these studies to assess efficacy.…”
mentioning
confidence: 99%
“…However, there is no evidence that they improve chronic postoperative pain. [108][109][110][111][112][113][114][115][116][117][118] Parasternal Intercostal and Paravertebral Blocks Parasternal intercostal and paravertebral blocks reduce acute postoperative pain. [119][120][121][122] Despite this, there is no evidence that either has an effect on chronic poststernotomy pain.…”
Section: Transdermal Lidocainementioning
confidence: 99%
“…? In this issue, Parlow et al 7 report that, in a retrospective audit of 131 consecutive elective cardiac surgical patients, their multimodal postoperative analgesic regimen (parasternal infiltration, acetaminophen and indomethacin, and postoperative iv morphine) allowed for uneventful early tracheal extubation. Lowdose ITM (259 ± 53 µg) further facilitated early tracheal extubation (75 ± 65 vs 117 ± 85 min) and reduced postoperative analgesic requirement (4.6 ± 4.1 vs 10.0 ± 14.8 mg), but did not shorten the hospital length of stay (LOS).…”
mentioning
confidence: 99%
“…R Ri is sq qu ue es s e et t a av va an nt ta ag ge es s d de e l la a m mo or rp ph hi in ne e i in nt tr ra at th hé éc ca al le e ( (M MI IT T) ) e en n c ca ar rd di io oc ch hi ir ru ur rg gi ie e Dans le présent numéro, Parlow et coll. 7 montrent que, dans un audit rétrospectif de 131 patients consé-cutifs en cardiochirurgie réglée, une analgésie postopératoire multimodale (infiltration parasternale, acétaminophène et indométacine, puis morphine iv postopératoire) a permis de réaliser une extubation trachéale précoce sans conséquence. Une faible dose de MIT (259 ± 53 µg) a facilité davantage l'extubation trachéale précoce (75 ± 65 vs 117 ± 85 min) et réduit les besoins analgésiques postopératoires (4,6 ± 4,1 vs 10,0 ± 14,8 mg), mais n'a pas raccourci la longueur du séjour (LDS) à l'hôpital.…”
unclassified